433 EVALUATION OF STEM CELL POPULATIONS IN THE BLOOD OF PATIENTS UNDERGOING EXTRACORPOREAL MEMBRANE OXYGENATION THERAPY. (1st January 2006) - Hendrickson, B.; Senadheera, D.; Hong, C.; Wang, X.; Lutzko, C.; Bui, K. C.
Abstract : Stem cell transplantation has successfully been used for a variety of hematologic and genetic diseases. There exists a tremendous interest in the development of stem cells for regenerative medicine. Previous studies have demonstrated tissue chimerism following solid organ transplantation in areas of chronic inflammation, suggesting that extrinsic cells may contribute to normal tissue remodeling and regeneration. This study evaluated whether stem cells circulate in the blood of patients with acute life-threatening heart and/or lung failure who received extracorporeal membrane oxygenation (ECMO) life support. In this pilot study, blood from the discarded ECMO circuits of five patients (age: 8 days to 13 months) and six umbilical cord blood (CB) controls were evaluated for stem cell activity. Flow cytometry analysis for CD34 expression and hematopoietic progenitor assays indicate that there are comparable numbers of hematopoietic progenitor cells in ECMO and CB controls. The blood samples were also analyzed for the presence of mesenchymal stem cells (MSCs). Three out of five ECMO blood samples yielded a total of twelve mesenchymal colonies compared to one out of six of CB yielding one colony. These MSC colonies were expanded in vitro for up to ten passages so far and were capable of chondrogenic, adipogenic, and osteogenic differentiation. Flow cytometric analysis demonstrated that the MSCs were negative for hematopoietic antigens: CD34, CD45, CD33, and CXCR4; and positive for known markers of MSCs: CD105 (SH2), CD29, and CD44. The average doubling time of these MSCs is about 2 days (50 hrs). In summary, we isolated hematopoietic progenitors and MSCs from the ECMO circuit blood of patients after ECMO therapy. We speculate that the tissue injury or organ failure for which patients are placed on ECMO and/or the physiologic demand from hemodilution with higher circulatory volume may stimulate the mobilization of these stem cells from the bone marrow. Whether or not these cells are capable of differentiation into pulmonary or cardiac phenotypes is not known. Further studies along this line of investigation may in the future translate into developing cell-based therapies for severe heart and lung disease.